Myokines and Their Potential Protective Role Against Oxidative Stress in Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) - José Luis Bucarey; Isis Trujillo-González; Evan M. Paules; Alejandra Espinosa (Antioxidants)
Myokines, bioactive peptides released by skeletal muscle, have emerged as crucial regulators of metabolic and protective pathways in peripheral tissues, particularly in combating oxidative stress and inflammation. Their plasma concentration significantly increases following exercise, offering valuable insights into the role of physical activity in preventing sarcopenia and mitigating metabolic diseases, including obesity, diabetes, and metabolic dysfunction-associated steatotic liver disease (MASLD). This review focuses on discussing the roles of specific myokines in activating intracellular signaling pathways within the liver, which confer protection against steatosis and lipid peroxidation. We detail the mechanism underlying lipid peroxidation and highlight the liver’s antioxidant defenses, such as glutathione (GSH) and glutathione peroxidase 4 (GPX4), which are pivotal in reducing ferroptosis. Furthermore, we provide an in-depth analysis of key myokines, including myostatin, brain-derived neurotrophic factor (BDNF), and irisin, among others, and their potential impact on liver function. Finally, we discuss the molecular mechanisms through which these myokines influence oxidate stress and lipid metabolism, emphasizing their capacity to modulate antioxidant responses in the liver. Finally, we underscore the therapeutic potential of exercise as a non-pharmacological intervention to enhance myokine release, thereby preventing the progression of MASD through improved hepatic antioxidant defenses. This review represents a comprehensive perspective on the intersection of exercise, myokine biology, and liver health.